Analysis of the Implementation of Digital Village in Socorejo Village, Tuban District - Rifqi Aji Saputra; Tukiman Tukiman (Jurnal Impresi Indonesia, 2024)
Socorejo Village is one of the areas that is able to implement a digital village in implementing E-Government for easy access to public services. This study aims to determine the implementation of digital village in Socorejo Village, Jenu Sub-district, Tuban Regency. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The focus of this research uses the theory of successful elements of E-Government implementation based on the results of studies and research at the Harvard JFK School of Government which consists of support, capacity and value. The results showed that the implementation of digital village in Socorejo Village can be said to be successful. This is because the Socorejo Village Government can fulfill the existing elements of success starting from support, adequate resource capacity and through the implementation of digital villages can provide benefits to the village government and the community. However, continuous and comprehensive socialization is needed and efforts are needed to improve both quality and quantity and maintenance in order to continue to support the sustainability of the digital village.